Effects of lecithin on growth and hematological indices in juveniles of Siberian sturgeon (Acipenser baeri Brandet 1869) - Najafipour Moghadam, E.; Falahatkar, B.; Kalbassi, M.R. (2011)
This study was carried out to evaluate the effects of dietary lecithin on growth performance and hematological indices in juveniles of Siberian sturgeon (Acipenser baeri). Fish with initial average weight of 32.9±0.3 grams were fed five isoproteic and isolipidic formulated diets with different soybean lecithin levels including 0, 2.5, 5, 7.5 and 10% in triplicate groups for 8 weeks. Results showed that lecithin supplementation to 7.5% significantly increased some growth indices such as body weight increase (BWI), specific growth rate (SGR), feed conversion ratio (FCR ) final weight (Wf), condition factor (CF) and protein efficiency ratio (PER). Also, increasing dietary lecithin to the level of 10% significantly decreased growth indices. According to the results of hematological assays, hemoglobin (Hb) in treatments of 5% and 7.5% in comparison to other treatments had higher value. Hematocrit (Hct) in fish fed with 7.5% lecithin was higher than those fed with 0 and 2.5% lecithin in the diets. Other hematological indices such as WBC, RBC, MCV, MCH and MCHC showed no significant differences among the treatments. In conclusion, the results of this study indicated that Siberian sturgeon juveniles have a relatively moderate lecithin requirement (between 5 and 7.5 percent of the diet) and these levels of lecithin in diet induces increase of growth performance and improves health status of this species. Published